Confirmed organophosphorus and carbamate pesticide poisonings in South African wildlife (2009–2014) - Christo J. Botha (Journal of the South African Veterinary Association, 2015)
During a six-year period (from January 2009 to December 2014), specimens collected from 344 cases of suspected organophosphorus and carbamate pesticide poisonings in wildlife, including birds, were submitted to the Toxicology Laboratory (ARC-OVI) for analysis. A positive diagnosis was made in 135 (39%) of these cases. The majority of cases were from birds, which included Cape vultures (Gyps coprotheres) and African white-backed vultures (Gyps africanus) and bateleur eagles (Terathopius ecaudatus). In one incident 49 vultures were killed when a farmer intentionally laced carcasses with carbofuran in an attempt to control jackal predation. There were 22 incidents of poisoning in helmeted guineafowl (Numida meleagris). On nine different occasions blue cranes (Anthropoides paradiseus) were poisoned, in one incident 14 birds were reported to have been killed. Over the period of investigation, there were 20 cases of poisoning involving mammalian species, the majority being vervet monkeys (Chlorocebus pygerythrus). The carbamate pesticides were responsible for 57 incidents of poisoning. Aldicarb, carbofuran and methomyl were detected in 26, 18 and 12 cases respectively. The majority of organophosphorus pesticide poisonings were caused by diazinon (n = 19), monocrotophos (n = 13) and methamidophos (n = 10).